Otter Lagoon - Deas, Mike, 1982-; Deas, Nancy (Deas, Mike, 1982- Sueño Bay adventures, 2021)
"In this graphic novel sequel for early middle readers, two young sleuths must figure out why their sleepy seaside town is being overrun by monsters."--